Organotypic rat slices cultured in human CSF -An evaluation using extracellular field recordings - Gustafsson, Andreas (My University, 2016)
This thesis present an investigation of a method for culturing hippocampal slices from rat in human cerebrospinal fluid. Slices were placed on Millipore™ membranes in wells cointaining human cerebrospinal fluid and incubated for 2-5 days. Control trials were made using Neurobasal-A as culture medium. The trials were evaluated using extracellular field recordings. In addition, pH and osmolarity in the culture media was monitored and used to adjust the culturing process. The study shows that preserving acute-like properties of cultured slices for a prolonged time is possible, but that the culturing method is not robust. Acute-like recordings from cultured slices were obtained, and slice properties were shown to be preserved and recorded over several days from the same culture well, but the successful trials were few. Overall performance of the culturing was found to be poor with many slices degenerating in the culturing process. The study points towards early problems during culturing, which needs to be followed up. Some possible future research topics for the field of organotypic slice culturing are discussed and suggested based on the findings of the study. In addition of the presentation of the research conducted, the thesis also covers a work conducted in connecting neuroscience and didactics. This was done in the form of teaching material on recent discoveries in neuroscience and their possible use for teaching methods. The material was attended for, and used in a course on learning theories given at the MPLOL master’s programme at Chalmers University of Technology.
Keywords: Annan data- och informationsvetenskap; Other Computer and Information Science